¿Cuál es el destino de los países abundantes en recursos minerales? Nueva evidencia sobre la relación entre recursos naturales, instituciones y crecimiento económico - Perla, Cecilia (2004)
Economies that have large endowments of natural resources, especially the ones that rely on oil and minerals, are ofien regarded as unlikely to develop, or even seen as cursed by nature. It is said that the mineral rents, which could be used to trigger a growth process, have in practice several negative effects that by and large counteract their potential positive contributions. Nevertheless, it seems that these results are sensitive to the measures of resource abundance that are used, and mineral resource abundance might not be necessarily growth retarding. This study will evaluate if the arguments to uphold that mineral rich countries are doomed to low economic growth are strong and sound by testing a number of robustness checks on the standard models of resources and growth. We test if there are any specification bias in the model proposed- in particular of omitted variables- and if the resource curse thesis remains robust when using other measures of resource abundance, and when testing specifically for a mineral resource curse.